2015
DOI: 10.13102/sociobiology.v62i4.807
|View full text |Cite
|
Sign up to set email alerts
|

Fast Food Delivery: Is There a Way for Foraging Success in Leaf-Cutting Ants?

Abstract: 2005). This assumption is strikingly evident for leaf-cutting ants who travel along trails hundreds of meters long (Lewis et al., 2008). Walking long distances through a trail system is an intrinsic feature of leaf-cutting ants. The main function of this trail system is to guide foragers between the nest and the resource patch (Shepherd, 1982; Fowler & Stiles, 1980). Foraging trails arise from the recruitment process, which involves outbound scouts, who are the first workers to leave the nest seeking food. Onc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Physical trails can have several functions for ant colonies. First, they offer a smooth substrate and thus allow ants to move faster from the food locations to their nest, to have a higher transport efficiency and to increase their food delivery rate (Sales et al 2015, Bouchebti et al 2018. Second, they allow colonies to share and gather information rapidly on the resources available in the environment (Shepherd 1982, Farji-Brener & Sierra 1998, Dussutour et al 2007, Farji-Brener et al 2010, Bouchebti et al 2015a.…”
Section: Introductionmentioning
confidence: 99%
“…Physical trails can have several functions for ant colonies. First, they offer a smooth substrate and thus allow ants to move faster from the food locations to their nest, to have a higher transport efficiency and to increase their food delivery rate (Sales et al 2015, Bouchebti et al 2018. Second, they allow colonies to share and gather information rapidly on the resources available in the environment (Shepherd 1982, Farji-Brener & Sierra 1998, Dussutour et al 2007, Farji-Brener et al 2010, Bouchebti et al 2015a.…”
Section: Introductionmentioning
confidence: 99%
“…Because they offer a relatively even surface, the use of trunk-trails allow ants to increase their speed (Rockwood & Hubbell 1987;Fewell 1988;Sales et al 2015;Bochynek et al 2017) and, probablythis has actually never been measuredto decrease the energetic cost of transport (Halsey 2016). Based on an estimation of the energetic cost of load transport, Howard (2001) showed that in leaf-cutting ants of the genus Atta the cost of construction and maintenance of physical trails may be relatively low compared to the huge number of workers in the colonies.…”
Section: Introductionmentioning
confidence: 99%
“…Acromyrmex foraging trails, as well as those of other ant species, present physical trails on the surface of the soil which are actively constructed by workers (Bruce and Burd, 2012) and vary in width and length (Sales et al, 2015;Lopes et al, 2016). They can be found in places with different physical characteristics which influence ant displacement.…”
Section: Introductionmentioning
confidence: 99%
“…They can be found in places with different physical characteristics which influence ant displacement. It is known, for example, that there is an increase in worker walking speed in physically delimited litter-free trails (Sales et al, 2015). This physical delimitation leads to a higher concentration of forager workers and a consequent increase in delivery rate to the colony, either due to an increase in the worker flow (Sales et al, 2015;Bochynek et al, 2017) or to the trail pheromone concentration (Jaffé and Howse, 1979;Sumpter, 2006).…”
Section: Introductionmentioning
confidence: 99%